The UN global compact fair competition and environmental and labour justice in international markets - Gonzalez-Perez, Maria Alejandra; Leonard, Liam. (Bingley, U.K. : Emerald, 2015)
Since UN Secretary-General Kofi Annan launched the Global Compact in 1999, over 12,000 organisations around the world have voluntarily adopted and promoted its values and Ten Principles in the areas of human rights, labour, environment and corruption. This corporate citizenship initiative has been seen as a non-compulsory alternative to international market regulations. Around the globe, the UN Global Compact has promoted the creation of local and regional networks for businesses to act together to mainstream the Ten Principles. This edited volume brings together international contributions on the specific implications for business when embracing the Global Compact. Managerial, internationalisation, legal, behavioural and sociological perspectives are explored in this volume in which both evidences and theoretical developments are reflected.
UN-supported principles for responsible management education (PRME) : global context, regional implementation, and the role of signatories / Anthony F. Buono, Jonas Haertle, Rudi Kurz -- How UN global compact can contribute corporate accountability and sustainability? / Arzu Özsözgün Çaliskan -- Creating alignment between corporate sustainability and global compact initiatives / Harish C. Chandan -- Designing corporate governance to enhance respect for UN global compact principles / Alice de Jonge -- Writing the social contract : integrating the UN global compact and mining CSR / W. Travis Selmier II -- Socially responsible investment : the financial performance of Spanish equity pension plans / Carmen-Pilar Martí-Ballester -- Why do Spanish firms engage in the global compact initiative? An explanation from institutional and social identity theories / Maria dels Angels Dasí Coscollar, Consuelo Dolz Dolz, Esmeralda Linares-Navarro -- How international investment agreements can better contribute to sustainable development by reflecting the U.N. global compact principles / Rafael Tamayo-Álvarez -- Leadership styles in organizations participating the UN global compact / Emel Esen -- The espoused values of MNEs operating in Colombia : their ethical orientation and stakeholder consideration / Sergio Castrillón-Orrego -- First contact pilot program : a contribution for the dissemination of the global compact in Medellin, Colombia / Juan Carlos Diaz Vasquez, Jaime Alberto Ospina Gallo, Margarita María Montoya Peláez.
Print version record
Keywords: Global Compact; Nature -- Environmental Conservation & Protection; Social impact of environmental issues; Leadership -- Moral and ethical aspects; Social responsibility of business